MENINGKATKAN HASIL BELAJAR SISWA MENGGUNAKAN STRATEGI READING GUIDE PADA MATA PELAJARAN PAI KELAS IV SDN 018 RAMBAH KECAMATAN RAMBAH KABUPATEN ROKAN HULU TAHUN PELAJARAN 2016/2017 - Erniza Gazali (STKIP ROKANIA, 2016)
This research is an action research (action research). Subjects in this study amounted to 24 people consisting of 13 men and 11 women, who are fourth grade students in academic year 2016/2017. The focus of this research is learning to use your reading strategies to increase learning outcomes in the fourth grade students SD Negeri 018 Rambah. Reading Strategy Guide is proven to improve student learning outcomes of the average grade 67.08 into 79.25 in the second cycle. The increase was 12.16